Strategy for Developing Shallots as a Regional Superior Commodity to Support Sustainability in Humbang Hasundutan Regency - Octasella Ainani As'ad; Supriadi Surbakti (ITScience (Information Technology and Science), 2026)
Shallots (Allium ascalonicum L.) are a strategic horticultural commodity that has high economic value and great potential to be developed in Humbang Hasundutan (Humbahas) Regency, North Sumatra. This regency has very supportive agro-ecological conditions, namely an altitude of 330–2,075 meters above sea level, temperatures ranging from 17°C–29°C, and land availability of 250,271.02 hectares. This study aims to: (1) analyse the potential and existing conditions of shallot development in Humbahas Regency; (2) identify internal and external factors that influence shallot development; (3) formulate a strategy for developing shallots as a sustainable regional superior commodity. The method used is qualitative and quantitative descriptive analysis with a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach and Location Quotient (LQ) analysis. The research results show that shallot productivity in Humbahas reaches 13 tons/ha under optimal conditions, with total food estate production for the 2020–2022 period reaching 165 tons. A SWOT analysis places Humbahas shallot development in the SO (Strength-Opportunity) quadrant, making an aggressive strategy the primary choice. Recommended strategies include: strengthening farmer institutions, adopting modern cultivation technology (True Shallot Seed/TSS), developing value chains and agro-industry, and consistent local government policy support to support the sustainability of shallot farming.